Acid recovery process based on nanofiltration-reverse osmosis
Through the nanofiltration-reverse osmosis process combined with extracted resin adsorption and diffusion dialysis, the acid recovery problem in the anodizing process is solved, and the efficient recovery of acid and aluminum ions is achieved, reducing costs and improving economic benefits.
Patent Information
- Application Number
- CN202411673376.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Traditional methods are difficult to efficiently recover the acid in the chemical waste liquid produced by the anodizing process, resulting in waste of resources and environmental pollution, and the process cost is relatively high.
The nanofiltration-reverse osmosis process is used to combine the adsorption, diffusion dialysis and evaporation concentration of extracted resin. The nanofiltration membrane and reverse osmosis membrane are prepared efficiently to achieve high-efficiency separation and recovery of acid and aluminum ions.
It realizes efficient recycling of acid and aluminum ions in chemical waste liquid, reduces costs and improves economic benefits, and has a simple process and no secondary recycling is required.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to an acid recovery process based on nanofiltration-reverse osmosis. Background Art
[0002] Anodizing is the most important aluminum alloy surface treatment technology, and is widely used in daily chemicals, automotive decorative parts, construction, aerospace industry, electrical and electronic industry, etc. Anodizing and polishing processes will continuously produce high-concentration waste acid liquid, and the traditional method of adding chemicals to treat waste acid liquid has a high treatment cost. Based on this, it is necessary to use other methods to recover the waste acid in anodizing polishing liquid.
[0003] At present, the acid recovery process of resin adsorption for aluminum removal can turn waste into treasure and make waste acid be utilized as a resource. It has the advantages of simple process, low energy consumption, and low equipment price, and has great value for promotion and application. However, the resin after adsorption needs to be desorbed and regenerated, which will produce a large amount of acid-containing desorption liquid. Therefore, solving the problem of acid recovery in the desorption liquid can further improve the economic benefits of chemical waste liquid recovery and reduce acid pollution. Summary of the invention
[0004] The object of the present invention is to provide an acid recovery process based on nanofiltration-reverse osmosis to achieve efficient recovery of acid in chemical polishing waste liquid generated by an anodic oxidation process.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] The present invention provides an acid recovery process based on nanofiltration-reverse osmosis, comprising the following steps:
[0007] Step 1: The waste liquid from chemical disposal is subjected to leaching resin to adsorb aluminum ions, and the effluent is evaporated and concentrated to be used as the acid solution in the chemical disposal tank;
[0008] Step 2: The adsorbed leaching resin is desorbed with distilled water, the obtained desorption liquid is subjected to diffusion dialysis to separate aluminum ions, and the recovered acid solution is separated by nanofiltration;
[0009] Step 3: The nanofiltration diluted liquid is concentrated by reverse osmosis to obtain concentrated acid solution, which is used as the recycled sulfuric acid desorption liquid;
[0010] Step 4: adding alkali to neutralize the diffusion dialysis residual liquid, the nanofiltration concentrate and the reverse osmosis dilute liquid to prepare an aluminum-containing flocculant.
[0011] The chemical waste liquid contains a large amount of sulfuric acid, phosphoric acid and aluminum ions. The leaching resin can adsorb aluminum ions through cation exchange, and the aluminum ion content in the effluent is greatly reduced. The acid concentration can be increased by evaporation and concentration as the acid liquid for recycling chemical waste tanks. After adsorption, the cation exchange resin needs to be desorbed and regenerated. The desorbed liquid is an acid solution containing a high concentration of aluminum ions. Most of the aluminum ions are blocked during diffusion dialysis, and the residual liquid is a solution containing a high concentration of aluminum ions. The acid concentration in the recovered acid solution is relatively high. Nanofiltration can further remove aluminum ions. The acid in the nanofiltration dilute liquid is concentrated by reverse osmosis to achieve the recovery of high-concentration acid.
[0012] Furthermore, in step 1, the ratio of the leaching resin to the chemical waste liquid is 0.03-0.05 g / mL, and the adsorption time of aluminum ions is 5-10 hours.
[0013] Furthermore, the nanofiltration membrane used in the nanofiltration is an amino-containing imidazolium salt-modified polyamide nanofiltration membrane.
[0014] Furthermore, the reverse osmosis membrane used in the reverse osmosis is a reverse osmosis membrane containing phosphoric acid-sulfonic acid bifunctional groups.
[0015] Furthermore, the total acid concentration in the chemical waste liquid is 3-30wt%, and the aluminum ion concentration is 1200-11000mg / L.
[0016] Furthermore, the phosphorus-sulfur ratio in the chemical waste liquid is 4-10.
[0017] Furthermore, the preparation steps of the leaching resin are as follows:
[0018] The AB-8 or X-5 resin is soaked in anhydrous ethanol at a concentration of 0.1-0.5 g / mL, and magnetically stirred for 1-4 hours. After reduced pressure filtration, the filter cake is rinsed twice with a 5-15wt% sodium carbonate solution, rinsed with ultrapure water until neutral, and dried at 50-70°C. After drying, it is placed in a beaker, and an extractant and anhydrous ethanol are added in sequence. The resin is magnetically stirred for 12-24 hours, and vacuum evaporated at 40-60°C in a rotary evaporator until the resin is fluffy, and dried at 50-60°C to obtain an leaching resin.
[0019] The adsorption resin is a leaching resin prepared by modifying the extractant, which has high selective adsorption to metallic aluminum ions, can achieve efficient adsorption of aluminum ions in acid solution, and improve the recovery rate of aluminum ions.
[0020] Furthermore, the extractant is one of TBP, P204 and Cyanex272, and the mass ratio of the extractant to the resin is 3-4:5.
[0021] Furthermore, the preparation steps of the nanofiltration membrane are as follows:
[0022] A 0.1-0.3wt% piperazine aqueous solution is poured onto a polysulfone-based membrane with a molecular weight cutoff of 200-500Da, the solution is removed after standing for 2-5 minutes, the membrane is dried at room temperature and immersed in a 0.1-0.5wt% trimesoyl chloride solution for interfacial polymerization for 1-2 minutes, the solution is removed, the membrane is dried at room temperature and immersed in a 2-5wt% 1-aminopropyl-3-methylimidazolium bromide aqueous solution, the membrane is allowed to stand for 10-30 minutes, the solution is removed, the membrane is dried at room temperature and washed with deionized water, and dried to obtain a nanofiltration membrane.
[0023] A polyamide nanofiltration membrane is prepared by interweaving piperazine and trimesoyl chloride on a polysulfone-based membrane through interfacial polymerization. After the interfacial polymerization, the unreacted acyl chloride groups on the membrane surface combine with the amine groups in 1-aminopropyl-3-methylimidazolium bromide due to the amidation reaction, fixing the positively charged imidazolium groups on the membrane surface, increasing the positive charge concentration on the nanofiltration membrane surface and enhancing the repulsion of metal ions. The imidazolium groups that do not participate in the interfacial polymerization cause the polyamide network pores to expand and provide more channels.
[0024] Furthermore, the solvent used in the trimesoyl chloride solution is one of n-hexane and dimethyl sulfoxide.
[0025] Furthermore, the preparation steps of the reverse osmosis membrane are as follows:
[0026] A 1-3wt% m-phenylenediamine aqueous solution is poured onto a polysulfone-based membrane with a molecular weight cutoff of 50-100Da, the solution is removed after standing for 2-5 minutes, the membrane is dried at room temperature and immersed in a 0.1-0.5wt% m-phenylenedisulfonyl chloride solution for interfacial polymerization for 1-2 minutes, the solution is removed, the membrane is dried at room temperature and immersed in a 2-4wt% ethylenediamine aqueous solution and the membrane is allowed to stand for 5-10 minutes, the membrane is washed three times with deionized water after the solution is removed and immersed in a 5-15wt% formaldehyde and phosphorous acid aqueous solution, the mass ratio of formaldehyde to phosphorous acid is 1:1-3, the membrane is immersed at 60-80°C for 3-5 hours, the membrane is washed with deionized water and dried to obtain a reverse osmosis membrane containing a phosphonic acid-sulfonic acid bifunctional group.
[0027] By introducing sulfonic acid groups and phosphoric acid groups on the reverse osmosis membrane, the acid retention rate can be improved by increasing the negative charge density on the membrane surface, thereby improving the hydrophilicity and selectivity of the membrane and effectively improving the water treatment efficiency.
[0028] Beneficial effects of the present invention:
[0029] (1) By combining adsorption, diffusion dialysis, nanofiltration and reverse osmosis processes, the acid and aluminum ions in the chemical waste liquid can be efficiently separated. The acid solution and aluminum ion solution of different concentrations produced in the recovery process can be actively reused to achieve efficient recovery of acid and aluminum ions, thereby reducing costs and increasing economic benefits.
[0030] (2) The preparation of polyamide nanofiltration membrane modified with imidazolium salt containing amino group and reverse osmosis membrane containing phosphonic acid-sulfonic acid bifunctional group can improve the retention of aluminum ions and the concentration of acid, increase the recovery rate, and do not require secondary recovery, and the process is simple. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] Preparation of leaching resin:
[0034] Take 100g of AB-8 resin and soak it in 200mL of anhydrous ethanol, stir it magnetically for 2h, filter it under reduced pressure, rinse the filter cake twice with 5wt% sodium carbonate solution, rinse it with ultrapure water until it is neutral, dry it at 50°C, place it in a beaker after drying, add 80g of TBP and 250mL of anhydrous ethanol in turn, stir it magnetically for 24h, evaporate it in a vacuum evaporator at 40°C until the resin is fluffy, and dry it at 50°C to obtain the leaching resin.
[0035] Preparation of nanofiltration membrane:
[0036] A 0.1wt% piperazine aqueous solution is poured on a polysulfone-based membrane with a molecular weight cutoff of 200-500Da, and the solution is removed after standing for 5 minutes. After drying at room temperature, the membrane is immersed in a 0.5wt% hexane solution of trimesoyl chloride for interfacial polymerization for 2 minutes. The solution is removed, the membrane is dried at room temperature, and the membrane is immersed in a 2wt% 1-aminopropyl-3-methylimidazolium bromide aqueous solution. The membrane is allowed to stand for 30 minutes. After removing the solution, the membrane is dried at room temperature, washed with deionized water, and dried to obtain a nanofiltration membrane.
[0037] Preparation of reverse osmosis membrane:
[0038] A 2wt% aqueous solution of m-phenylenediamine is poured onto a polysulfone-based membrane with a molecular weight cutoff of 50-100Da, the solution is removed after standing for 2 minutes, the membrane is dried at room temperature and immersed in a 0.1wt% solution of m-phenylenedisulfonyl chloride for interfacial polymerization for 2 minutes, the solution is removed, the membrane is dried at room temperature and immersed in a 3wt% aqueous solution of ethylenediamine and the membrane is allowed to stand for 5 minutes. After removing the solution, the membrane is washed three times with deionized water and immersed in a 10wt% aqueous solution of formaldehyde and phosphorous acid, with a mass ratio of formaldehyde to phosphorous acid of 1:1, and immersed at 70°C for 3 hours. The membrane is washed with deionized water and dried to obtain a reverse osmosis membrane containing a phosphonic acid-sulfonic acid bifunctional group.
[0039] The total acid concentration of the chemical waste liquid provided in this embodiment is 4.13wt%, the aluminum ion concentration is 1211.9mg / L, the phosphorus-sulfur ratio is 4, and the acid is recovered by the following process steps:
[0040] Step 1: Fill the leaching resin prepared in the embodiment into the resin column, and the chemical waste liquid passes through the bed filled with the resin from bottom to top in countercurrent, the ratio of the leaching resin to the chemical waste liquid is 0.03 g / mL, the flow rate is about 2.33 mL / min, and a total of 1 L of chemical waste liquid is injected. The leaching resin adsorbs aluminum ions, and the effluent is evaporated and concentrated as the reused chemical waste tank acid liquid;
[0041] Step 2: Wash the adsorbed leaching resin with distilled water from top to bottom until the acid and aluminum ion concentrations in the desorption liquid are reduced to the minimum, and then stop desorption. Collect the desorption liquid and transport it to a diffusion dialysis device. Diffusion dialysis is used to separate aluminum ions. The bilateral flow ratio is set to 1:1, the desorption liquid flux is set to 0.34 L / h, and the outlet recovery acid solution and residual liquid flow ratio is about 1.3:1. The recovered acid solution is collected and transported to a nanofiltration device for separation. The nanofiltration uses the nanofiltration membrane prepared in this embodiment. The aluminum retention rate of the nanofiltration is 98.9%, and the total acid permeability is 82.5%;
[0042] Step 3: The nanofiltration diluted liquid is concentrated by reverse osmosis to obtain concentrated acid solution. The reverse osmosis adopts the reverse osmosis membrane prepared in Example 1. The total acid permeability of the reverse osmosis is 6.2%, and the aluminum retention rate is 92.3%. The concentrated acid solution is used as the recycled sulfuric acid desorption liquid;
[0043] Step 4: preparing an aluminum-containing flocculant by neutralizing the diffusion dialysis residual liquid, the nanofiltration concentrate and the reverse osmosis dilute liquid with alkali.
[0044] By detecting the mass concentration of total acid in the effluent after leaching resin adsorption, the mass concentration of total acid in the concentrated acid solution, the aluminum ion concentration in the diffusion dialysis residual liquid, the aluminum ion concentration in the nanofiltration concentrate and the aluminum ion concentration in the reverse osmosis weak liquid, the total acid recovery rate in the acid recovery process of Example 1 was obtained to be 93.3%, and the aluminum ion recovery rate was 87.6%.
[0045] Example 2
[0046] The difference from Example 1 is that TBP in the preparation of the leaching resin is replaced by P204, and the other steps and conditions are the same as in Example 1.
[0047] Correspondingly, due to the change in the adsorption performance of the leaching resin, the concentration of the desorption liquid after desorption changes, affecting the parameters of the subsequent processes. Among them, the aluminum retention rate of nanofiltration is 98.3%, the total acid permeability is 84.4%, the total acid permeability of reverse osmosis is 5.9%, and the aluminum retention rate is 92.0%.
[0048] The total acid recovery rate in the acid recovery process of this embodiment is 92.7%, and the aluminum ion recovery rate is 85.0%.
[0049] Example 3
[0050] The difference from Example 1 is that TBP in the preparation of the leaching resin is replaced by Cyanex272, and the other steps and conditions are the same as in Example 1.
[0051] Correspondingly, due to the change in the adsorption performance of the leaching resin, the concentration of the desorption liquid after desorption changes, affecting the parameters of the subsequent processes. Among them, the aluminum retention rate of nanofiltration is 99.2%, the total acid permeability is 80.6%, the total acid permeability of reverse osmosis is 6.5%, and the aluminum retention rate is 92.5%.
[0052] The total acid recovery rate in the acid recovery process of this embodiment is 93.9%, and the aluminum ion recovery rate is 88.7%.
[0053] Example 4
[0054] The difference from Example 3 is that the concentration of the 1-aminopropyl-3-methylimidazolium bromide aqueous solution is increased to 4 wt % in the preparation of the nanofiltration membrane, and the other steps and conditions are the same as those in Example 3.
[0055] Correspondingly, due to the change in the separation performance of the nanofiltration membrane, the concentration of the nanofiltration dilute liquid after nanofiltration changes, affecting the parameters of the subsequent processes. Among them, the aluminum retention rate of nanofiltration is 99.6%, the total acid permeability is 83.4%, the total acid permeability of reverse osmosis is 6.6%, and the aluminum retention rate is 92.2%.
[0056] The total acid recovery rate in the acid recovery process of this embodiment is 94.5%, and the aluminum ion recovery rate is 92.4%.
[0057] Example 5
[0058] The difference from Example 3 is that the concentration of the 1-aminopropyl-3-methylimidazolium bromide aqueous solution is increased to 5 wt % in the preparation of the nanofiltration membrane, and the other steps and conditions are the same as those in Example 3.
[0059] Correspondingly, due to the change in the separation performance of the nanofiltration membrane, the concentration of the nanofiltration dilute liquid after nanofiltration changes, affecting the parameters of the subsequent processes. Among them, the aluminum retention rate of nanofiltration is 99.5%, the total acid permeability is 83.2%, the total acid permeability of reverse osmosis is 6.3%, and the aluminum retention rate is 92.3%.
[0060] The total acid recovery rate in the acid recovery process of this embodiment is 94.0%, and the aluminum ion recovery rate is 91.1%.
[0061] Example 6
[0062] The difference from Example 4 is that the concentration of the ethylenediamine aqueous solution in the preparation of the reverse osmosis membrane is reduced to 2wt%, and the concentration of the formaldehyde and phosphorous acid aqueous solutions is reduced to 5wt%. The other steps and conditions are the same as in Example 4.
[0063] Accordingly, due to the change in the separation performance of the reverse osmosis membrane, the total acid permeability of the reverse osmosis was 5.0% and the aluminum rejection was 92.5%.
[0064] The total acid recovery rate in the acid recovery process of this embodiment is 96.7%, and the aluminum ion recovery rate is 92.0%.
[0065] Example 7
[0066] The difference from Example 4 is that the concentration of the ethylenediamine aqueous solution in the preparation of the reverse osmosis membrane is increased to 4wt%, and the concentration of the formaldehyde and phosphorous acid aqueous solutions is increased to 15wt%. The other steps and conditions are the same as in Example 4.
[0067] Correspondingly, due to the change in the separation performance of the reverse osmosis membrane, the total acid permeability of the reverse osmosis was 4.7% and the aluminum rejection was 92.6%.
[0068] The total acid recovery rate in the acid recovery process of this embodiment is 97.0%, and the aluminum ion recovery rate is 91.9%.
[0069] Comparative Example 1
[0070] Compared with Example 1, the 1-aminopropyl-3-methylimidazolium bromide aqueous solution was not added in the preparation of the nanofiltration membrane in this comparative example, and the other steps and conditions were the same as those in Example 1.
[0071] Preparation of nanofiltration membrane:
[0072] A 0.1wt% piperazine aqueous solution is poured onto a polysulfone-based membrane with a molecular weight cutoff of 200-500Da, and the solution is removed after standing for 5 minutes. After drying at room temperature, the membrane is immersed in a 0.5wt% hexane solution of trimesoyl chloride for interfacial polymerization for 2 minutes. After removing the solution, the membrane is dried at room temperature, washed with deionized water, and dried to obtain a nanofiltration membrane.
[0073] Correspondingly, due to the change in the separation performance of the nanofiltration membrane, the concentration of the nanofiltration dilute liquid after nanofiltration changes, affecting the parameters of the subsequent processes. Among them, the aluminum retention rate of nanofiltration is 90.7%, the total acid permeability is 63.3%, the total acid permeability of reverse osmosis is 6.1%, and the aluminum retention rate is 92.2%.
[0074] The total acid recovery rate in the acid recovery process of this comparative example is 85.0%, and the aluminum ion recovery rate is 74.7%.
[0075] Comparative Example 2
[0076] Compared with Example 1, the reverse osmosis membrane prepared in this comparative example does not include the addition of ethylenediamine aqueous solution and formaldehyde and phosphorous acid aqueous solution, and the other steps and conditions are the same as those in Example 1.
[0077] Preparation of reverse osmosis membrane:
[0078] A 2wt% aqueous solution of m-phenylenediamine was poured onto a polysulfone-based membrane with a molecular weight cutoff of 50-100Da, and the solution was removed after standing for 2 minutes. After drying at room temperature, the membrane was immersed in a 0.1wt% solution of m-phenylenedisulfonyl chloride for interfacial polymerization for 2 minutes, and the solution was removed. The membrane was washed with deionized water and dried to obtain a reverse osmosis membrane.
[0079] Correspondingly, due to the change in the separation performance of the reverse osmosis membrane, the total acid permeability of the reverse osmosis was 10.6% and the aluminum rejection was 92.1%.
[0080] The total acid recovery rate in the acid recovery process of this comparative example is 88.5%, and the aluminum ion recovery rate is 87.9%.
[0081] It can be seen from the processing data results in the examples that the acid recovery rate of Example 7 is the highest. In Examples 1 to 3, when the extractant is Cyanex272, the extraction performance of aluminum ions is the best, and the recovery rate of aluminum ions is the highest. Examples 4 and 5 increase the density of the imidazolium group loaded on the nanofiltration membrane by increasing the concentration of the aqueous solution of 1-aminopropyl-3-methylimidazolium bromide salt on the basis of Example 3, thereby improving the repulsion of metal ions. In Example 4, the aluminum ion recovery rate is as high as 92.4%. In Example 7, the negative charge density on the surface of the reverse osmosis membrane is increased, and the total acid recovery rate is significantly improved compared with Example 4. In the comparative example, the nanofiltration membrane and the reverse osmosis membrane are not modified, and the recovery efficiency of the process is far inferior to that of Example 1.
[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An acid recovery process based on nanofiltration-reverse osmosis, characterized in that: The following steps are involved: Step 1: The waste liquid from chemical disposal is subjected to leaching resin to adsorb aluminum ions, and the effluent is evaporated and concentrated to be used as the acid solution in the chemical disposal tank; Step 2: The adsorbed leaching resin is desorbed with distilled water, the obtained desorption liquid is subjected to diffusion dialysis to separate aluminum ions, and the recovered acid solution is separated by nanofiltration; Step 3: The nanofiltration diluted liquid is concentrated by reverse osmosis to obtain concentrated acid solution, which is used as the recycled sulfuric acid desorption liquid; Step 4: adding alkali to neutralize the diffusion dialysis residual liquid, the nanofiltration concentrate and the reverse osmosis dilute liquid to prepare an aluminum-containing flocculant.
2. The acid recovery process based on nanofiltration-reverse osmosis according to claim 1, characterized in that: In step 1, the ratio of the leaching resin to the chemical waste liquid is 0.03-0.05 g / mL, and the adsorption time of aluminum ions is 5-10 hours.
3. The acid recovery process based on nanofiltration-reverse osmosis according to claim 1, characterized in that: The nanofiltration membrane used in the nanofiltration is an imidazolium salt-modified polyamide nanofiltration membrane containing amino groups.
4. The acid recovery process based on nanofiltration-reverse osmosis according to claim 1, characterized in that: The reverse osmosis membrane used in the reverse osmosis is a reverse osmosis membrane containing phosphoric acid-sulfonic acid bifunctional groups.
5. The acid recovery process based on nanofiltration-reverse osmosis according to claim 1, characterized in that: The total acid concentration in the chemical waste liquid is 3-30wt%, and the aluminum ion concentration is 1200-11000mg / L; The phosphorus-sulfur ratio in the chemical waste liquid is 4-10.
6. The acid recovery process based on nanofiltration-reverse osmosis according to claim 1, characterized in that: The preparation steps of the leaching resin are as follows: The AB-8 or X-5 resin is soaked in anhydrous ethanol at a concentration of 0.1-0.5 g / mL, and magnetically stirred for 1-4 hours. After reduced pressure filtration, the filter cake is rinsed twice with a 5-15wt% sodium carbonate solution, rinsed with ultrapure water until neutral, and dried at 50-70°C. After drying, it is placed in a beaker, and an extractant and anhydrous ethanol are added in sequence. The resin is magnetically stirred for 12-24 hours, and vacuum evaporated at 40-60°C in a rotary evaporator until the resin is fluffy, and dried at 50-60°C to obtain an leaching resin.
7. The acid recovery process based on nanofiltration-reverse osmosis according to claim 6, characterized in that: The extractant is one of TBP, P204 and Cyanex272, and the mass ratio of the extractant to the resin is 3-4:
5.
8. The acid recovery process based on nanofiltration-reverse osmosis according to claim 1, characterized in that: The preparation steps of the nanofiltration membrane are as follows: A 0.1-0.3wt% piperazine aqueous solution is poured onto a polysulfone-based membrane with a molecular weight cutoff of 200-500Da, the solution is removed after standing for 2-5 minutes, the membrane is dried at room temperature and immersed in a 0.1-0.5wt% trimesoyl chloride solution for interfacial polymerization for 1-2 minutes, the solution is removed, the membrane is dried at room temperature and immersed in a 2-5wt% 1-aminopropyl-3-methylimidazolium bromide aqueous solution, the membrane is allowed to stand for 10-30 minutes, the solution is removed, the membrane is dried at room temperature and washed with deionized water, and dried to obtain a nanofiltration membrane.
9. The acid recovery process based on nanofiltration-reverse osmosis according to claim 8, characterized in that: The solvent used in the trimesoyl chloride solution is one of n-hexane and dimethyl sulfoxide.
10. The acid recovery process based on nanofiltration-reverse osmosis according to claim 1, characterized in that: The preparation steps of the reverse osmosis membrane are as follows: A 1-3wt% m-phenylenediamine aqueous solution is poured onto a polysulfone-based membrane with a molecular weight cutoff of 50-100Da, the solution is removed after standing for 2-5 minutes, the membrane is dried at room temperature and immersed in a 0.1-0.5wt% m-phenylenedisulfonyl chloride solution for interfacial polymerization for 1-2 minutes, the solution is removed, the membrane is dried at room temperature and immersed in a 2-4wt% ethylenediamine aqueous solution and the membrane is allowed to stand for 5-10 minutes, the membrane is washed three times with deionized water after the solution is removed and immersed in a 5-15wt% formaldehyde and phosphorous acid aqueous solution, the mass ratio of formaldehyde to phosphorous acid is 1:1-3, the membrane is immersed at 60-80°C for 3-5 hours, the membrane is washed with deionized water and dried to obtain a reverse osmosis membrane containing a phosphonic acid-sulfonic acid bifunctional group.
Citation Information
Patent Citations
Method for repairing mine chrome heavy metal pollution soil
CN105880271A
Use and method of neutral phosphine extractant used for extracting and separating cerium (IV) or thorium (IV)
CN107287419A
Method and system for resourceful treatment of phosphate wastewater by using resin coupling membrane process
CN115196768A
Method for selectively extracting lithium from levextrel resin
CN115717200A
Chemical polishing waste acid recovery treatment method
CN116253469A
Cited By
Sulfonic acid ionic membrane forming equipment and use method thereof
CN121161287A
Solid-state radiation grafting method of phosphonic acid-sulfonic acid bifunctional ionic membrane
CN121550848A
